LmxM.22.0250-Encoded Dual Specificity Protein/Lipid Phosphatase Impairs Leishmania mexicana Virulence In Vitro - Kraeva, Natalya (Pathogens, 2019)
Protein phosphorylation/dephosphorylation is an important regulatory mechanism that controls many key physiological processes. Numerous pathogens successfully use kinases and phosphatases to internalize, replicate, and survive, modifying the host′s phosphorylation profile or signal transduction pathways. Multiple phosphatases and kinases from diverse bacterial pathogens have been implicated in human infections before. In this work, we have identified and characterized the dual specificity protein/lipid phosphatase LmDUSP1 as a novel virulence factor governing Leishmania mexicana infection. The LmDUSP1-encoding gene (LmxM.22.0250 in L. mexicana) has been acquired from bacteria via horizontal gene transfer. Importantly, its orthologues have been associated with virulence in several bacterial species, such as Mycobacterium tuberculosis and Listeria monocytogenes. Leishmania mexicana with ablated LmxM.22.0250 demonstrated severely attenuated virulence in the experimental infection of primary mouse macrophages, suggesting that this gene facilitates Leishmania pathogenicity in vertebrates. Despite significant upregulation of LmxM.22.0250 expression in metacyclic promastigotes, its ablation did not affect the ability of mutant cells to differentiate into virulent stages in insects. It remains to be further investigated which specific biochemical pathways involve LmDUSP1 and how this facilitates the parasite′s survival in the host. One of the interesting possibilities is that LmDUSP1 may target host′s substrate(s), thereby affecting its signal transduction pathways.